TEORI MODEL KEPERAWATAN MYRA ESTRIN LEVINA - Raudatul Jannah; Irna Nursanti (Nusantara Hasana Journal, 2024)
This paper aims to explore the application of Myra Estrin Levine’s conservation nursing model theory in the nursing care of patient with dextra pedis cellulitis. Cellulitis is a bacterial infection of the skin and underlying tissue that can cause redness, swelling, blistering and pain when pressed. Generally, cellulitis occurs on the skin of the lower legs, but can also appear on the skin of the face, arms, eyes and stomach. Myra Estrin Levine’s conservation theory is divided into 4 conservation principles, namely energy needs and their use, social integrity, structural integrity and personal integrity. The core definition of Levine’s theory is that care is interaction between human, she uses the concept of adaptation and increasing the body’s response through a system approach. Myra Estrin Levine’s concept model is divided into wholeness (holism), adaptation and conservation. The concept of wholeness refers to efforts to understand and care for patients as individuals who are complete and integrated in all aspects of their lives. Nurses are expected to engage patients in care that considers physical, emotional, social and spiritual dimensions. The importance of wholeness is to respect the individual as a complex unit, where nurses strive to understand the context of the patient’s life and provide care that does not only focus on symptoms or disease, but also pays attention to broader aspects of the patient’s life. According to Levine’s nursing theory, adaptation is an individual’s effort to maintan balance and stability in response to environmental stimuli.